2000
DOI: 10.1590/s0074-02762000000500002
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Trypanosoma cruzi clonal genotypes (clonet 20 and 39) isolated from Bolivian triatomines following subculture in liquid medium

Abstract: Previous studies showed that two groups of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 28 publications
4
34
1
Order By: Relevance
“…Our group verified that in mixed infections, interactions between populations of T. cruzi may occur, resulting in important changes in the biological characteristics of the parasite and the evolution of the infection (12,25,32). Moreover, the importance of mixed infections in the epidemiology of Chagas' disease (8,35) and the evidence that they may result in significant alterations in the host-parasite relationship motivated the studies on the efficacy of chemotherapy in dual infections. Therefore, the goal of the present investigation was to evaluate in BALB/c mice the impact of dual T. cruzi infections on chemotherapy effectiveness, compared with the respective single infections with stocks from distinct major T. cruzi genotypes.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Our group verified that in mixed infections, interactions between populations of T. cruzi may occur, resulting in important changes in the biological characteristics of the parasite and the evolution of the infection (12,25,32). Moreover, the importance of mixed infections in the epidemiology of Chagas' disease (8,35) and the evidence that they may result in significant alterations in the host-parasite relationship motivated the studies on the efficacy of chemotherapy in dual infections. Therefore, the goal of the present investigation was to evaluate in BALB/c mice the impact of dual T. cruzi infections on chemotherapy effectiveness, compared with the respective single infections with stocks from distinct major T. cruzi genotypes.…”
Section: Discussionsupporting
confidence: 59%
“…These findings may also represent a multifactorial phenomenon, and we cannot discount the possibility of parasite selection at the beginning of the infection, prior to the establishment of BZ treatment. Moreover, there is also the possibility of parasite selection during the isolation procedures and during in vitro growth before microsatellites characterization (8,13) or even the unavailability of blood to specific T. cruzi stocks sequestered in tissue sites (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar problems were encountered with the dixenous species of medical importance (Dukes et al, 1991;Bosseno et al, 2000;Dey et al, 2002). Application of PCR-based techniques showed that mixed infection with up to four different salivarian trypanosomes in the same insect vector are possible (Stevens et al, 1994;Masiga et al, 1996;Jamonneau et al, 2004), and multiple cases of inter-and intraspecies mixed infections have also been reported in animals (Reifenberg et al, 1997;Jamonneau et al, 2004;Njiokou et al, 2004).…”
Section: Introductionmentioning
confidence: 86%
“…The same stocks were also analyzed by multilocus enzyme electrophoresis, demonstrating a high degree of heterogeneity that was not related to geographic origin (12). Analysis of minicircle kDNA variability among Mexican stocks showed no correlation between the sequence homologies of the hypervariable region of minicircles and clustering (2), contrasting with results obtained for South American stocks (3,4).…”
mentioning
confidence: 86%